Profiling the Governance System of Local School Boards in Democratic Republic of Congo (Global Journal of Human-Social Science, 2019)
In many developing countries such as RD Congo where parents are the main source of school financing, the Local School Board (LSB) is strategic governance body where the parents exercise participation rights of decision-making in management of school resources (financial, human and materiel) and the control of teaching quality and quantity. The purpose of this quantitative study is to test the possible differences between the Governance System of LSB of 16 pilot primary schools (7 higher performance schools and 9 lower performance schools). The findings of the survey conducted from 224 LSB members help to describe and explain the profiles of effective governance systems of LSB in order to inspire the LSB of lower performance schools and stakeholders.
Keywords: pilot school; school board; local school board; school board governance